Degradation of o-Nitro Acetanilide by Heterogeneous Photocatalysis - Joshi, J.D.; Vora, Jabali; Sharma, Sangita; C. Patel, Chirag; Patel, Ashok (Asian Journal of Chemistry, 2010)
The photocatalytic degradation ofo-nitro acetanilide, on semiconductor zinc oxide powder in heterogeneous conditions was studied. Concentration of substrate, amount of semiconductor, pH, light intensity, sensitizers, etc. parameters were found to affect the kinetics of the degradation process. A probable mechanism for the process is proposed.